PENGARUH MODEL ACTIVE LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMP PADA PEMBELAJARAN IPS - Dela Tarisa Agustiandini; Toto Nusantara (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
ABSTRACT Social studies learning should extend beyond content mastery when the ability to assess issues, weigh reasons, and make decisions constitutes an essential learning outcome. This study examines the effect of the active learning model on the critical thinking skills of seventh-grade students at SMPN 25 Malang, with the intervention implemented through a series of collaborative, contextual, and exploratory learning activities. A quasi-experimental approach using a non-equivalent control group design was applied to 31 students in the experimental group and 32 students in the control group. Students’ critical thinking skills were assessed through an essay test based on six indicators, while changes in achievement were analyzed using a Paired Samples T-Test and the magnitude of the effect was calculated using Cohen’s d. The experimental group demonstrated a significant effect (Sig. = 0.000), with a Cohen’s d of 2.783, categorized as a very large effect, whereas the control group did not show a significant improvement. These findings indicate that active learning can create learning experiences that more effectively support the development of critical thinking skills than conventional instruction. The findings offer an alternative approach to social studies learning that positions student engagement as part of the development of twenty-first-century thinking competencies. The primary implication is the need for learning experiences that provide students with opportunities to process information and construct reasoned judgments independently. ABSTRAK Pembelajaran IPS tidak cukup mengarahkan siswa pada penguasaan materi ketika kemampuan menilai persoalan, mempertimbangkan alasan, dan menentukan keputusan menjadi bagian dari capaian belajar. Penelitian ini menelaah pengaruh model active learning terhadap kemampuan berpikir kritis siswa kelas VII SMPN 25 Malang, dengan perlakuan yang diwujudkan melalui rangkaian aktivitas kolaboratif, kontekstual, dan eksploratif. Pendekatan quasi-experimental dengan non-equivalent control group design diterapkan pada 31 siswa kelompok eksperimen dan 32 siswa kelompok kontrol. Kemampuan berpikir kritis diukur melalui tes esai yang mengacu pada enam indikator, kemudian perubahan capaian dianalisis menggunakan Paired Samples T-Test dan kekuatan pengaruh dihitung melalui Cohen's d. Perubahan pada kelompok eksperimen menunjukkan pengaruh yang signifikan (Sig. = 0,000) dengan Cohen's d sebesar 2,783 dalam kategori sangat besar, sedangkan kelompok kontrol tidak mengalami peningkatan yang signifikan. Temuan ini mengindikasikan bahwa active learning dapat menciptakan pengalaman belajar yang lebih mendukung perkembangan kemampuan berpikir kritis dibandingkan pembelajaran konvensional. Hasil tersebut menawarkan alternatif bagi pembelajaran IPS yang menempatkan keterlibatan siswa sebagai bagian dari proses pengembangan kompetensi berpikir abad ke-21. Implikasi utamanya terletak pada perlunya pengalaman belajar yang memberi kesempatan kepada siswa mengolah informasi dan membangun alasan secara mandiri.